My mini book of numbers (Say Publishing Karachi, 2011)
This mini book introduces young learners to the fascinating world of numbers. Through engaging illustrations and simple text, children will explore the concept of numbers, counting, and basic arithmetic operations. Each page features a different number, accompanied by a corresponding quantity of objects to reinforce understanding. The book aims to spark curiosity and foster a love of mathematics in young minds.